2020
DOI: 10.3390/molecules25092229
|View full text |Cite
|
Sign up to set email alerts
|

Computational Methods for the Identification of Molecular Targets of Toxic Food Additives. Butylated Hydroxytoluene as a Case Study

Abstract: Butylated hydroxytoluene (BHT) is one of the most commonly used synthetic antioxidants in food, cosmetic, pharmaceutical and petrochemical products. BHT is considered safe for human health; however, its widespread use together with the potential toxicological effects have increased consumers concern about the use of this synthetic food additive. In addition, the estimated daily intake of BHT has been demonstrated to exceed the recommended acceptable threshold. In the present work, using BHT as a case study, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 104 publications
0
10
0
1
Order By: Relevance
“…Synthetic antioxidants such as butylated hydrox-ianisole (BHA), butylated hydroxytoluene (BHT) and propyl gallate are commonly used in edible oils but their use is discouraged due to their possible ill health effects (Aluyor and Ori-Jesu, 2008;Tortosa et al, 2020). The studies revealed that these synthetic antioxidants are prone to degradation and converted into decomposition products at frying temperatures (Abusaloua et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic antioxidants such as butylated hydrox-ianisole (BHA), butylated hydroxytoluene (BHT) and propyl gallate are commonly used in edible oils but their use is discouraged due to their possible ill health effects (Aluyor and Ori-Jesu, 2008;Tortosa et al, 2020). The studies revealed that these synthetic antioxidants are prone to degradation and converted into decomposition products at frying temperatures (Abusaloua et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic phenolic antioxidants were developed in the late 1940s [ 1 ]. They have been used in food, pharmaceuticals, cosmetic, and petrochemical industries to increase shelf life and to improve the quality, freshness, taste, and texture of consumer products [ 2 ]. They are widely used to trap free radicals and delay lipid oxidation in various products [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 25 ] However, BHT, BHA, and TBHQ are currently allowed in Canada, United States, Korea, and certain countries within the European Union [ 1 , 3 , 26 , 27 ]. They are categorized as “generally recognized as safe” (GRAS) by the U.S. Food and Drug Administration (FDA) and safe to use in cosmetics by the Cosmetic Ingredient Review (CIR) Expert Panel [ 1 , 2 , 6 , 26 ], while the International Agency for Research on Cancer (IARC) classifies BHT as non-carcinogenic (based on limited evidence), BHA as reasonably anticipated to be a human carcinogen and TBHQ as not carcinogenic [ 13 , 16 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ya que a la mayoría de PUP se les agregan AS, su ingestión puede ser subestimada. La ingestión real de antioxidantes es poco conocida ya que existe falta de información sobre la exposición humana a estos compuestos (Tortosa et al 2020). La carencia de la información real de la cantidad de AS adicionados a los alimentos que derivan de la canasta básica mexicana, así como la concentración, provoca que estimar la IDA en la población mexicana sea un proceso incierto.…”
Section: Resultsunclassified